2015
DOI: 10.18869/acadpub.jafm.67.221.22802
|View full text |Cite
|
Sign up to set email alerts
|

Navier-Stokes Flow in Cylindrical Elastic Tubes

Abstract: Analytical expressions correlating the volumetric flow rate to the inlet and outlet pressures are derived for the time-independent flow of Newtonian fluids in cylindrically-shaped elastic tubes using a one-dimensional Navier-Stokes flow model with two pressure-area constitutive relations. These expressions for elastic tubes are the equivalent of Poiseuille and Poiseuille-type expressions for rigid tubes which were previously derived for the flow of Newtonian and non-Newtonian fluids under various flow conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The Newtonian formulae can be used as an alternative to the previously derived formulae [17] which are based on the 1D Navier-Stokes flow in distensible tubes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Newtonian formulae can be used as an alternative to the previously derived formulae [17] which are based on the 1D Navier-Stokes flow in distensible tubes.…”
Section: Discussionmentioning
confidence: 99%
“…In [17] two formulae based on the widely used 1D Navier-Stokes model for the flow of Newtonian fluids in elastic tubes were derived. These formulae, which are based on the first and second p-A relations respectively, are given by…”
Section: Comparison To 1d Navier-stokes Modelmentioning
confidence: 99%
“…The effect of peristalsis on Herschel -Bulkley fluid flow in an elastic tube was discussed by Vajravelu et al (2014). Sochi (2015) derived analytical expressions for the Newtonian flow characteristics by considering cylindrically shaped elastic tubes. Shen et al (2016) presented an elastic tube model to study the pulsatile flow characteristics of blood by taking arterial wall motion in to consideration.…”
Section: Introductionmentioning
confidence: 99%
“…where G is a constant, it can be shown that Equation 5 can be reduced to two independent variational forms d dr γ dµ dr = 0 (7) and d dr µ dγ dr = 0 (8)…”
Section: Variational Methodsmentioning
confidence: 99%